Public health implications of severe floods in Pakistan: assessing the devastating impact on health and the economy - Raza, Mahnoor; Fatima, Alina; Habiba, Ume; Shah, Hussain Haider (Frontiers in Environmental Science, 2023)
Disastrous Flooding, Humanitarian crisis, Pakistan, Infectious outbreaks, Public Health